2020
DOI: 10.1155/2020/2749105
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Arrhenius Kinetics on Multiphase Flow between a Pair of Rotating Circular Plates

Abstract: In this study, we aim to deal with the flow behavior betwixt a pair of rotating circular plates filled with Carreau fluid under the suspension of nanoparticles and motile gyrotactic microorganisms in the presence of generalized magnetic Reynolds number. The activation energy is also contemplated with the nanoparticle concentration equation. The appropriate similarity transformations are used to formulate the proposed mathematical modeling in the three dimensions. The outcomes of the torque on both plates, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Brasseaur et al 25 investigated the significance of two‐layered peristaltic pumping of viscous fluids in a channel. The peristaltic motion of two‐layered flows was also studied by Ramachandra Rao and Usha, 26 Usha and Ramachandra Rao, 27 Misra and Pandey, 28 Vajravelu et al, 29,30 Sreenadh et al, 31 Abd Elmaboud et al, 32 Zeeshan et al, 33 Alolaiyan et al, 34 Ijaz et al, 35 Arain et al, 36 and Ali et al 37,38 …”
Section: Introductionmentioning
confidence: 90%
“…Brasseaur et al 25 investigated the significance of two‐layered peristaltic pumping of viscous fluids in a channel. The peristaltic motion of two‐layered flows was also studied by Ramachandra Rao and Usha, 26 Usha and Ramachandra Rao, 27 Misra and Pandey, 28 Vajravelu et al, 29,30 Sreenadh et al, 31 Abd Elmaboud et al, 32 Zeeshan et al, 33 Alolaiyan et al, 34 Ijaz et al, 35 Arain et al, 36 and Ali et al 37,38 …”
Section: Introductionmentioning
confidence: 90%
“…Working in the domain of nonlinear fluid flows creates challenges to the mathematician and simulation engineers with its diversity and complexity. As the complexity of such fluids offers no unique constitutive equation which encounters all the properties, for such fluids, several non-Newtonian models are presented in [1][2][3][4]. e polymeric liquids reveal diverse rheological attributes apparent in the flow, such as polymer accumulation, mechanical mortification, and solvent composition.…”
Section: Introductionmentioning
confidence: 99%
“…He declared that DTM is more powerful technique [34,35]. In the study [36], Arain et al studied the flow behavior of Carreau fluid along rotating circular plates with gyrotactic microorganisms under the effects of magnetic generalized Reynolds # and concluded that fluid viscosity declines in shear thinning case when comparing with Newtonian and shear thickening fluids.…”
Section: Introductionmentioning
confidence: 99%